2013
DOI: 10.12988/ams.2013.13033
|View full text |Cite
|
Sign up to set email alerts
|

Waves dynamics in a linearized mud-flow Shallow model

Abstract: The study of formation and evolution of waves in mud-flows is strongly motivated by their destructive power. The rheology of these flows, which involve massive solid transport, is often described using linear or non-linear viscoplastic models. The paper analyzes the wave dynamics of mud-flows, presenting the linearized response of the 1D uniform flow of a viscoplastic fluid with yield stress, i.e. Herschel & Bulkley fluid, to a pointwise impulsive forcing term. The solution in either linearly stable or unstabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
(75 reference statements)
2
5
0
Order By: Relevance
“…1b suggests that the secondary wave attenuates more strongly than the primary one. Such a result is in agreement with the waves dynamics in linearized (laminar and turbulent) clear-water and mud flows investigated through the study of the Green's function [11,12,33]. Moreover, while for high values of wave periods the primary wave travels downstream without attenuating (Fig.…”
Section: Full Dynamic Modelsupporting
confidence: 88%
See 2 more Smart Citations
“…1b suggests that the secondary wave attenuates more strongly than the primary one. Such a result is in agreement with the waves dynamics in linearized (laminar and turbulent) clear-water and mud flows investigated through the study of the Green's function [11,12,33]. Moreover, while for high values of wave periods the primary wave travels downstream without attenuating (Fig.…”
Section: Full Dynamic Modelsupporting
confidence: 88%
“…(9). Moreover, in order to consider only linearly stable conditions (r < 0), the Froude number of the corresponding uniform condition is always assumed below the following neutral stability value [9,12]:…”
Section: Linear Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As far as stable base flow is considered (Fig.4a), the instantaneous maximum perturbation height progressively moves from the downstream ray x′/t′=c 1 towards the one corresponding to the kinematic wave celerity x′/t′ = c * . Similarly to [15], it may be shown that the Green function tends to assume asymptotically in time a Gaussian shape with the centroid moving with c * . Consistently, the Green function tends to vanish at the two boundaries of the characteristic fan.…”
Section: Resultsmentioning
confidence: 95%
“…However, the complete solution of the corresponding linearized flow model has not been deduced. As far as the impermeable bed case is concerned, the solution of the linearized flow model allowed to enlighten the essential flow features of the waves for both Newtonian [17,18,38,34,13,14] and non-Newtonian [11,15,16] fluids.…”
Section: Introductionmentioning
confidence: 99%